Minimum standards on prevention, diagnosis and treatment of occupational and work‐related skin diseases in Europe – position paper of the COST Action StanDerm (TD 1206). (June 2017) - Alfonso, J.H.; Bauer, A.; Bensefa‐Colas, L.; Boman, A.; Bubas, M.; Constandt, L.; Crepy, M.N.; Goncalo, M.; Macan, J.; Mahler, V.; Mijakoski, D.; Ramada Rodilla, J.M.; et al.
Abstract: Background: Skin diseases constitute up to 40% of all notified occupational diseases in most European countries, predominantly comprising contact dermatitis, contact urticaria, and skin cancer. While insufficient prevention of work‐related skin diseases (WRSD) is a top‐priority problem in Europe, common standards for prevention of these conditions are lacking. Objective: To develop common European standards on prevention and management of WRSD and occupational skin diseases (OSD). Method: Consensus amongst experts within occupational dermatology was achieved with regard to the definition of minimum evidence‐based standards on prevention and management of WRSD/OSD. Results: By definition, WRSDs/OSDs are (partially or fully) caused by occupational exposure. The definition of OSD sensu stricto additionally includes diverging national legal requirements, with an impact on registration, prevention, management, and compensation. With the implementation of the classification of WRSD/OSD in the International Classification of Diseases (ICD) 11th Revision in future, a valid surveillance and comparability across countries will be possible. Currently, WRDS and OSD are still under‐reported. Depending on legislation and regulations, huge differences exist in notification procedures in Europe, although notification is crucial to prevent chronic and relapsing disease. Facilities for early diagnosis, essential for individual patient management, should be based on existing guidelines and include a multidisciplinary approach. Patch testing is essential if contact dermatitis persists or relapses. Workplace exposure assessment of WRSD/OSD requires full labelling of product ingredients on material safety data sheets helping to identify allergens, irritants and skin carcinogens. Comparable standards in primary, secondary and tertiary prevention must be established in Europe to reduce the burden of WRSD/OSD in Europe. Conclusion: The adoption of common European standards on prevention of WRSD/OSD will contribute to reduce the incidence of OSD and their socio‐economic burden.